2012
DOI: 10.1186/1756-0500-5-529
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in preschool children (2–5 year-olds) in Birjand, Iran

Abstract: BackgroundChildhood overweight and obesity have increased progressively in developing countries and nowadays they are considered as a global epidemic.The aim of the present study was to determine prevalence of overweight and obesity in 2–5 year-old children in kindergartens of Birjand in 2008.FindingsThis cross- sectional and descriptive- analytical study was conducted on 500 children, who were 2–5 years-old, in kindergartens of Birjand selected through census. It was found that prevalence of overweight was 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
6
15
0
Order By: Relevance
“…Children with high birth weight were more at risk of overweight than children with normal birth weight. These findings are consistent with previous reports [ 14 , 17 , 38 , 39 ]. However, some studies have shown that low birth weight is associated with a higher risk of overweight or obesity, [ 33 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…Children with high birth weight were more at risk of overweight than children with normal birth weight. These findings are consistent with previous reports [ 14 , 17 , 38 , 39 ]. However, some studies have shown that low birth weight is associated with a higher risk of overweight or obesity, [ 33 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…An earlier adipose rebound increases the risk of later obesity ( 23 ). A study in China indicated that the age of adiposity rebound was 4 years in boys and 3 years in girls ( 24 ), and the same was seen in a study in Iran ( 25 ). In the present cross-sectional study, a cohort effect could to some extent be contributing to the increasing trend.…”
Section: Discussionsupporting
confidence: 58%
“…This finding is consistent with many studies [19,20,21], but in contrast with reports with girl obesity predominance [22][23][24][25][26] and no gender difference noticed among boys and girls [27,28]. It is well known that overweight is a result of interactions between genetic and environmental factors, metabolism, eating and physical activity behaviour, and social and individual psychology [29][30][31][32] It has been found that parent rental is a risk factor of obesity, infact our study area is a rural area where only civil servant with high incomes are transferred for professional reasons and are obliged to rent houses because they are not in their native village.…”
Section: Discussion:-supporting
confidence: 82%